HUBUNGAN PERSEPSI SISWA TERHADAP STRATEGI PEMBELAJARAN GURU DENGAN HASIL BELAJAR SENI RUPA DI SMP N 10 PADANG - Sri Wahyuni; Ernis Ernis (Universitas Negeri Padang, 2020)
This research goals to investigate the relationship between students' perceptions of teacher’s teach strategies and learning outcomes of Art and Culture subject matter Fine Arts, at SMP Negeri 10 Padang. The research is a correlational research with quantitative approach. This study used the product moment correlation analysis technique. The population was 800 students of SMP Negeri 10 Padang to determine the sample using the